Clinical case of Surgical Treatment of Coronary Heart Disease in an Adult Patient with the Anterior Descending Artery Originating from the Right Sinus of Valsalva - O. M. Dovgan; A. P. Fedorchuk; S. V. Varbanets; Y. O. Chernetsky (Український журнал серцево-судинної хірургії, 2019)
Abnormal coronary artery origins can occur both in isolation and in combination with congenital heart defects. In the vast majority of cases, such anomalies can affect the deterioration of coronary blood flow with ischemic manifestations. The report describes effort angina in an adult patient who in the childhood underwent operation for the congenital heart defect because of inter-arterial compression of the left anterior descending artery originating with a separate mouth from the right sinus of Valsalva.